Fixed point theory for weakly sequentially upper semicontinuous maps with applications to differential inclusions - Agarwal, R.P.; O'Regan, D. (Нелінійні коливання, 2002)
We present new fixed point theorems for weakly sequentially upper semicontinuous maps. These results are then used to establish existence principles for second order differential equations and inclusions. Наведено новi теореми про нерухому точку для слабко секвенцiйно напiвнеперервних вiдображень. Цi результати застосовано для доведення принципiв iснування для диференцiальних рiвнянь та включень другого порядку.